2010
DOI: 10.4103/1319-3767.65187
|View full text |Cite
|
Sign up to set email alerts
|

Exaggerated liver injury induced by renal ischemia reperfusion in diabetes: Effect of exenatide

Abstract: Background/Aim:This study was designed to investigate the possible effect of exenatide (Glucagon like Peptide-1 receptor agonist) on liver injury (distant organ) induced by renal ischemia reperfusion (IR) in diabetic rats.Materials and Methods:In vivo renal IR was performed in both type 2 diabetic and normal rats. Each protocol comprised ischemia for 30 minutes followed by reperfusion for 24 hours and a treatment period of 14 days before induction of ischemia.Results:Lipid peroxidation, xanthine oxidase activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 29 publications
4
28
0
Order By: Relevance
“…These results are in accordance with Mahfoudh-Boussaid et al (2012), Vaghasiya et al (2010) and Şener et al (2005) results. Moreover, bilateral renal I/R showed a cardiac oxidative stress injury indicated by a significant increase in the cardiac tissue LPO level, as well as a significant decrease in cardiac antioxidant enzymes, GR, SOD and CAT, levels compared to the control groups.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in accordance with Mahfoudh-Boussaid et al (2012), Vaghasiya et al (2010) and Şener et al (2005) results. Moreover, bilateral renal I/R showed a cardiac oxidative stress injury indicated by a significant increase in the cardiac tissue LPO level, as well as a significant decrease in cardiac antioxidant enzymes, GR, SOD and CAT, levels compared to the control groups.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, bilateral renal I/R showed a cardiac oxidative stress injury indicated by a significant increase in the cardiac tissue LPO level, as well as a significant decrease in cardiac antioxidant enzymes, GR, SOD and CAT, levels compared to the control groups. These results are in line with Vaghasiya et al (2010). This could be explained by the cardiac lesions following acute renal I/R injury, evidenced by the increase in cardiac tissue LPO and the decrease in cardiac tissue antioxidants.…”
Section: Discussionsupporting
confidence: 88%
“…Data are meanGS.E.M., nZ10, * or # P!0.05, **P!0.01 and *** or Vaghasiya et al (2010). In exenatide-treated diabetic rats, there were significant decreases in serum levels of alanine and aspartic aminotransferases, cholesterol, triglyceride, uric acids, blood urea nitrogen and creatinine compared with untreated diabetic rats.…”
Section: Figurementioning
confidence: 97%
“…The effect of exenatide on pancreatic b-cell differentiation after PDX1 stimulation may occur via protein kinase B and cAMP-dependent mechanisms (Drucker 2003a, Holz 2004). Moreover, exenatide may initiate its action on pancreatic b-cells via the stimulation of PI3K/PKB, a cell protecting system, and/or through the suppression of the caspase-3 apoptotic pathway (Vaghasiya et al 2010).…”
Section: Effect Of Exenatide On Gene Expression Of Selected Moleculesmentioning
confidence: 99%
“…Exendin-4 is an United States Food and Drug Administration (FDA) approved glucagon-like peptide-1 that increases insulin-dependent glycogen synthesis and the liver’s glucose uptake [3]. In one study, exendin-4 demonstrated a reduction in ROS generation and an enhancement effect on antioxidant enzyme activity, such as SOD, GPX, and CAT in rats [4]. Exendin-4 has been used for glucose stimulated insulin secretion, gastric emptying, and appetite suppression in type 2 diabetic patients.…”
Section: Introductionmentioning
confidence: 99%